The challenges of inclusive industrial development in South Africa's clothing and textile sector - Wesi, Boingotlo (My University, 2022)
South Africa’s clothing and textile sector has undergone a recovery process form nearly disappearing to reaching a stable condition. Over the years policies have been implemented to aid the sector and make it more competitive. However, the sector continues to be faced with developmental challenged. The study finds that within the clothing and textile sector, industrial policy has played an inadequate role as a tool of development and transformation. Secondly, the political economy of financing has been challenged as a result of pressures from transformational policies such as B-BEE. Lastly, there is a need for a policy agenda shift from competitiveness to transformation in South Africa’s clothing and textile sector.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, 2022
Keywords: Clothing and textile sector; South Africa; Industrial policy